Transformasi Manajemen Pendidikan Islam di Era Disrupsi Digital: Kajian Pustaka Kritis - Siswadi, Renalda; Riyadi, Riyadi; Jamilus, Jamilus (Indo-MathEdu Intellectuals Journal, 2025)
The development of digital technology and the wave of global disruption require Islamic educational institutions to adapt dynamically without losing their spiritual essence and Islamic values. This study aims to explain the concept of Islamic education in the era of disruption, identify the challenges faced by Islamic educational institutions, and analyse relevant change management models in the transformation process. This study uses the library research method with a critical analysis approach to various literature discussing change theory, education management, and Islamic values. The study focuses on the interpretation and relevance of change theories such as the Lewin, Kotter, and ADKAR models in the context of Islamic education, particularly how these theories can be integrated with the religious principles that form the basis of Islamic education. The results of the study indicate that the success of digital transformation in Islamic educational institutions requires visionary, adaptive leadership rooted in spirituality. The integration of modern change management principles and Islamic values, such as amanah (responsibility), musyawarah (collaboration), and ihsan (professionalism with worship value), forms the foundation for sustainable, meaningful change oriented towards the formation of Islamic character.